PENANAMAN MANGROVE SEBAGAI UPAYA MENCEGAH ABRASI DI DESA SERUNI MUMBUL, KECAMATAN PRINGGABAYA - Huda Ramadhanisa Sukma Dika, Nabila (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
The decline in the mangrove ecosystem is a problemimportant in Seruni Mumbul Village because of the many land conversionsresidential location. The aim of planting mangroves in this coastal zoneis for protection of coastlines from abrasion and restoration processesmangrove forest habitat in the Seruni Mumbul Village area, a natural barrieragainst flooding and providing habitat for various types of plants andfauna. Mataram University PMD KKN Service Activities toPeople in Seruni Mumbul Village in the context of planting seedsMangroves on the Coast which will be implemented on January 31 2024.The data used in mangrove planting is primary dataand secondary data. Primary data was obtained from field observations andinterviews, while secondary can be obtained from literature reviews, the webinternet and online journals. The results obtained from planting were 180Mangrove seeds have been prepared for planting, by plantingcarried out by taking into account the measured distance and the ecosystemMangroves in coastal areas will become more stable the more they are covered bymangrove forest. The mangrove ecosystem in Mandar Dalam Hamletits development experienced growth constraints caused byHuman activity, namely the conversion of land for settlement.